Analisis Konsep Circular Airport Untuk Wilayah Kepulauan Indonesia - Freddy Franciscus; Aprilia Sakti K (Jurnal Teknologi Kedirgantaraan, 2020)
The Circular Airport Concept, issued by Hessellink in 2014, attracted the attention and differed opinions of airport experts. Until now this project is still ongoing. This paper makes a preliminary analysis of the application of the concept of a circular airport in the Indonesian Archipelago. Building an airport in a limited area is a big challenge. Development of several pioneering routes that connect the regions with small aircraft continues to be done. Another challenge in airport construction is environmental sustainability. The circular airport concept is expected to be the right solution for the Indonesian Archipelago. Discussion included technical and safety analysis related to airport design, aircraft characteristics, Air Traffic Management [ATM} and also analysis of the environment and regional population to be developed.